Profil klorofil selada laut Ulva sp. dengan umur panen yang berbeda pada budidaya terkontrol - Zunnuraini Zunnuraini; Nunik Cokrowati; Nanda Diniarti (Universitas Sam Ratulangi, 2023)
This study aimed to analyze the growth of sea lettuce Ulva sp. with different harvest ages and the chlorophyll content in sea lettuce Ulva sp. with different harvest ages. The method used was an experimental method using a completely randomized design with a cultivation period of 45 days. The results showed the highest growth of Ulva sp. was in treatment D (40 days) with an average specific growth of 3,7%, absolute growth of 45,33 g, thallus length 5,6 cm, thallus width 8.1 cm, and chlorophyll content of 6,52 mg/l. In treatment B (20 days), the average specific growth was 2,8%, absolute growth was 32 g, thallus length was 4,6 cm, thallus width was 6,2 cm, and chlorophyll content was 6,24 mg/l. In treatment C (30 days) the average specific growth was 1,9%, absolute growth was 21,33 g, thallus length was 3,1 cm, thallus width was 5 cm, and chlorophyll content was 6,06 mg/l. In treatment A (10 days) the average specific growth was 1,5%, absolute growth was 16,33 g, thallus length was 2,7 cm, thallus width was 3,1 cm, and chlorophyll content was 3,78 mg/l. As conclusion, different harvest ages have a significant effect on the amount of chlorophyll content, absolute weight and specific growth rate of Ulva sp. The highest amount of chlorophyll content was found in treatment D of 6,52 mg/L, absolute weight growth of 45,33 g, specific growth rate of 3,7%. Keywords: Ulva sp, photosynthesis, growth, aquaculture